2008
DOI: 10.1111/j.1399-3054.2008.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

The FRO2 ferric reductase is required for glycine betaine’s effect on chilling tolerance in Arabidopsis roots

Abstract: FRO2 (At1g01580) codes for an NADPH-dependent ferric reductase in plasma membranes of root epidermal cells with a demonstrated role in iron uptake by plants. Ferric reductase activity has been shown to be the rate-limiting step for iron uptake in strategy I plants like Arabidopsis and in rice, but it has been unclear whether FRO genes have other physiological functions. We hypothesized that FRO2 was involved in chilling stress tolerance because its expression was upregulated by treatment of plants with glycine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 33 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Moreover, the reduction was higher under severe Cr (500 µM) stress as compared to lower Cr Similarly, Einset et al (2008) reported that GB might activate the expression of genes of ROS scavenging enzymes which protects the photosynthetic machinery from damage under stressful conditions. In present study, increase in plant growth and biomass might be due to decreased Cr concentration in plants ( Figure 5) and enhanced the activities of antioxidant enzymes (Figure 4).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the reduction was higher under severe Cr (500 µM) stress as compared to lower Cr Similarly, Einset et al (2008) reported that GB might activate the expression of genes of ROS scavenging enzymes which protects the photosynthetic machinery from damage under stressful conditions. In present study, increase in plant growth and biomass might be due to decreased Cr concentration in plants ( Figure 5) and enhanced the activities of antioxidant enzymes (Figure 4).…”
Section: Discussionmentioning
confidence: 94%
“…Because both foliar-applied GB and genetically generated GB in the cytosol are transported into chloroplasts, even if only to a small extent (Chen and Murata 2011;Park et al 2006). In addition, GB, either applied exogenously or synthesized in vivo in transgenic plants, can also activate specific genes which wholly or partly regulated a reduction in the stress-induced accumulation of ROS (Allard et al 1998;Einset and Connolly 2009;Einset et al 2007Einset et al , 2008Kathuria et al 2009;Park et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Einset et al . (2007, 2008) demonstrated, in Arabidopsis , that exogenous application of 100 m m GB to both leaves and roots improved tolerance of roots to chilling stress via regulation of the expression of a number of stress‐tolerance genes.…”
Section: Gb‐enhanced Tolerance To Abiotic Stress Is Associated With Imentioning
confidence: 99%
“…In the case of the FRO2 gene for ferric reductase, the FRO‐null mutant, frd1‐ 1, failed to respond to GB in chilling assays in terms both of recovery of root growth and of inhibition of the accumulation of ROS (Einset et al . 2008).…”
Section: Gb‐enhanced Tolerance To Abiotic Stress Is Associated With Imentioning
confidence: 99%
See 1 more Smart Citation